Estrategias de control para la contribución al cumplimiento de las acciones del proyecto educativo institucional de la escuela de educación básica Enrique Augusto Castro Aguilar periodo lectivo 2020-2021 - Yaguana Carpio, Mayra Gisela (My University, 2020)
The challenge to face: the resistance to social changes, the fractures in educational innovation and the lack of actions that modify the insufficiency of teachers determined to place in the PEI the possibility of a sustainable process of growth in the areas managed by the institution. For this challenge, the study appreciated as a scientific problem: What control strategies to implement in the Institutional Educational Project where the philosophical and pedagogical foundations that support the strategic conception managed by the educational institution are regulated and potentiated? The objective was set: Propose control strategies to the Institutional Strategic Plan based on philosophical and pedagogical foundations to obtain a transformative change in the educational situation of the “Enrique Castro Aguilar” school. This idea was investigated through the interview, survey, modeling and validation of experts. As main results, the study provides the novelty of considering strategies with a comprehensive approach because it is based on an epistemological perspective of the pedagogical and the philosophical to identify the objective reality of the school, including the perceptions of the subjects involved. It was determined that such matrices are generated from the Institutional Educational Project as a means of managing the strategic educational quality whose control, when assigned to a model, represents a theoretical contribution that can be socialized; also practical since it enables everyone's participation. The model for the control of the strategies has a logic that goes from the control to the correction mediated by the knowledge of the deviations in the application of the scientific method.
El desafío de enfrentar: la resistencia a los cambios sociales, las fracturas en la innovación educativa y la carencia de acciones que modifiquen la insuficiencia en los docentes determinó colocar en el PEI la posibilidad de un proceso sostenible de crecimiento de los ámbitos que gestiona la institución. Para ese reto el estudio apreció como problema científico: ¿Qué estrategias de control implementar al Proyecto Educativo Institucional donde se regulen y potencialicen los fundamentos filosóficos y pedagógicos que dan sustento a la concepción estratégica que gestiona la institución educativa? Se trazó como objetivo: Proponer estrategias de control al Plan Estratégico Institucional sustentadas en fundamentos filosóficos y pedagógicos para la obtención de un cambio transformador de la situación educativa de la escuela “Enrique Castro Aguilar”. Esta idea se investigó mediante la entrevista, la encuesta, la modelación y la validación de expertos. Como resultados principales el estudio aporta la novedad de considerar las estrategias con un enfoque integral porque se sustenta en una perspectiva epistemológica de lo pedagógico y lo filosófico para identificar la realidad objetiva de la escuela, incluidas las percepciones de los sujetos involucrados. Fue determinado que tales matrices se generan desde el Proyecto Educativo Institucional como medio gestor de la calidad educativa estratégica cuyo control al adjudicársele a un modelo representa un aporte teórico susceptible de socializar; asimismo práctico ya que viabiliza la participación de todos. El modelo para el control de las estrategias posee una lógica que va desde el control hasta la corrección mediatizado por el conocimiento de los desvíos en la aplicación del método científico.
Keywords: PEI; GESTION; CONTROL; ESTRATEGIA